Modeling of dynamic fracture mechanism in rock masses due to wave propagation - Abdallah, Mirvat; Haidar, Fatima (International Journal of Engineering and Technology, 2018)
Finding a new oil well is a stimulating experience at all levels, however, itâ€™s only an important milestone on the road towards exploiting oil and gas. When it comes to well drilling, the condition of the ground that surrounds the oil plays a major role. While there are many factors that dictate the success of exploring and drilling wells, porosity and permeability of the surrounding stone are some of the most important components.This paper focuses on the effective way to increase the porosity and the permeability of the rock using explosives without damaging the rock. In order to reach our aim, a numerical simulation was conducted. In fact, a 2D distinct element code was used, and 4 models were constructed; in each model the number of explosives increase while the blast load per explosive decreases.The dynamic stresses, and velocity vectors of the wave propagation were analyzed to evaluate the behavior of rock masses in each model. Moreover, a grid of history points was studied in order to compare the results and find the most suitable method to increase the crack propagation, therefore, the porosity and permeability along the rock masses, without damaging it.Â Â